Student Care Patterns in Integrated Islamic Boarding School Bina Amal Semarang - Aji Sofanudin; Rahmawati Prihastuty; Hamidulloh Ibda (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2021)
This research aims to determine caring patterns for student in an integrated Islamic boarding school (SMIT) Bina Amal Semarang. Teacher act as parents in this caring activity to conduct supervision, guidance, discipline, giving reward and punishment. SMIT Bina Amal Semarang is an integrated boarding Islamic school which consists of junior and senior high schools. By using qualitative approach, the research found that caring patterns at these schools were developed in a democratic pattern of pesantren model. All students of the schools were automatically deemed as “santri”(students) of the “pesantren” Bina Amal. Supervision, guidance, discipline, reward and punishment implemented at the Bina Amal Semarang schools were carried out by caregivers along with a clear organizational management consisting of three coordinators: Islamic culture and discipline coordinator, tahsin tahfiz coordinator, and academic coordinator. The rules were strictly enforced through student management guidelines that contain academic guidelines and dormitory rules. Learning system was integrated between school and dormitory programmes. Penelitian ini bertujuan untuk mengetahui pola asuh peserta didik Sekolah Menengah Islam Terpadu (SMIT) Bina Amal Semarang. Pola asuh merupakan cara guru sebagai orang tua dalam melakukan pengawasan, bimbingan, disiplin, pemberian hadiah dan hukuman yang diterapkan kepada peserta didik. SMIT Bina Amal Semarang merupakan Sekolah Islam Terpadu yang dikelola dengan sistem asrama (boarding school) terdiri atas jenjang SMP dan SMA. Dengan menggunakan pendekatan kualitatif temuan penelitian menunjukkan bahwa pola asuh peserta didik pada SMIT Bina Amal Semarang menerapkan pola demokratis model pesantren. Seluruh peserta didik SMIT Bina Amal otomatis adalah “santri” pada “pesantren” Bina Amal. Pengawasan, bimbingan, disiplin, pemberian hadiah dan hukuman yang diterapkan di Bina Amal Semarang dilakukan oleh pengasuh beserta organ struktur organisasi yang jelas: korbid budaya Islami dan kedisiplinan, korbid tahsin tahfiz, dan korbid akademik. Aturan diterapkan secara ketat melalui pedoman pengelolaan peserta didik yang berisi pedoman akademik dan tata kehidupan asrama. Pembelajaran peserta didik terintegrasi antara kegiatan pembelajaran sekolah dan kegiatan santri di asrama.